Kajian Hadis di Era Global: [Hadith Studies in the Global Era] - Muhammad Alfatih Suryadilaga (UIN Sunan Kalijaga Yogyakarta, 2014)
Hadith as the teachings of Islam which is one of the relics of the Prophet Muhammad has been progressing in the contemporary era. Both accessing and searching to study Hadith has easily carried out via the internet. The ease of access is not only in terms of searching Hadith and books of traditions and knowledge; it also found that certain software can be used to assess the Hadith authentication. Moreover, one easily assess a particular Hadith which in earlier times is very unlikely can be assessed. That is something on which to base any fundamental change in the development of fundamental traditions that become the dynamic tradition in the era of Dirasah al-Islamiyya. This study could be found in scientific journals that developed in the tradition of knowledge in PTAI in Indonesia and abroad. There is a tremendous development of the study compared to the studies that have been done earlier scholars. Existing studies do not just dwell on the text alone but goes beyond the text, which is in the public domain. This study became known as living traditions. In addition to the tradition, it raises another tradition that is the study of Hadith through serious study on the books of Hadith both in Indonesia and in Brunei Darussalam.[Hadis sebagai ajaran Islam yang merupakan salah satu peninggalan dari Nabi Muhammad saw. telah mengalami perkembangan di era kekinian. Akses dalam pencarian hadis dan studi hadis dengan mudah ditemukan melalui media internet. Kemudahan akses tersebut tidak hanya dalam hal pencarian hadis dan kitab-kitab hadis dan ilmunya saja. Selain itu juga ditemukan software tertentu yang dapat dijadikan untuk menilai otentifikasi hadis. Lebih dari itu, seseorang dengan mudah mengkaji kitab hadis tertentu yang pada zaman sebelumnya sangat tidak mungkin dapat dikaji. Hal tersebut merupakan sesuatu yang menjadi dasar adanya perubahan yang sangat mendasar dalam perkembangan hadis yang sangat mendasar sehingga menjadi adanya kajian hadis yang sangat dinamis yang masuk di era al-Dirasah Islamiyyah. Kajian ini terdapat dalam jurnal ilmiah yang berkembang dalam tradisi keilmuan di PTAI di Indonesia maupun luar negeri. Terdapat perkembangan kajian yang luar biasa dari kajian yang telah dilakukan ulama sebelumnya. Kajian yang ada tidak hanay berkutat pada teks semata melainkan sudah melampaui teks, yakni berada di ranah masyarakat. Kajian ini kemudian dikenal dengan living hadis. Selain tradisi tersebut, memunculkan tradisi lain yaitu adanya kajian kitab hadis melalui pengkajian yang serius atas kitab-kitab hadis baik yang ada di Indonesia maupun di negera Brunei Darussalam.]